2021
DOI: 10.12697/fce.2021.58.21
|View full text |Cite
|
Sign up to set email alerts
|

Bryophyte species and communities on various roofing materials, Estonia

Abstract: Considering the recent growth of interest in using mosses in creating vegetated green roofs, we set the aim of our study to get an overview of the variety of moss and liverwort species and communities growing spontaneously on roofs. Data were collected from 67 roofs of five different types of materials: fibre cement, bitumen, stone, thatched and steel from Tallinn and rural areas on Hiiumaa Island and in South Estonia. Indicator species analysis, MRPP, cluster analysis and ordination metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Indeed, research should be addressed to explore more suitable species to a specific regional climate (or even better, to the near future change of regional climate), but an assessment of species ranges is strictly recommended to avoid the risk of introducing a possible invasive alien plant (i.e., a moss outside its natural range and harmful to the local biodiversity). The selection of moss species is therefore a crucial way for developing technological greenery that is efficient and attractive to the market, but scientific research is currently on potential candidates 76 and few studies are directly based on comparative experiments among moss species. 77 Species selection is linked to develop and test cultivation methods on a broad-scale for moss.…”
Section: Synoptic Table and Future Workmentioning
confidence: 99%
“…Indeed, research should be addressed to explore more suitable species to a specific regional climate (or even better, to the near future change of regional climate), but an assessment of species ranges is strictly recommended to avoid the risk of introducing a possible invasive alien plant (i.e., a moss outside its natural range and harmful to the local biodiversity). The selection of moss species is therefore a crucial way for developing technological greenery that is efficient and attractive to the market, but scientific research is currently on potential candidates 76 and few studies are directly based on comparative experiments among moss species. 77 Species selection is linked to develop and test cultivation methods on a broad-scale for moss.…”
Section: Synoptic Table and Future Workmentioning
confidence: 99%
“…SLA, dispersal type, canopy height and seed mass were extracted from the LEDA database (Kleyer et al, 2008), whilst life form was extracted from Grime et al (2007) (see Table 1 for summary). The bryophyte searches did not yield useful information, although several of the returned papers used Ellenberg indicator values (e.g., Rajandu et al, 2021;Rola et al, 2021); however, these are considered to be ecological preferences rather than plant traits and we did not consider these further (Violle et al, 2007). Instead, we selected traits based on similar studies investigating succession found using alternate search terms in Google Scholar (Fernández-Martínez et al, 2019;Laine et al, 2018;Monteiro et al, 2020).…”
Section: Species Traitsmentioning
confidence: 99%
“…BNF in mosses was first attributed to cyanobacteria living on the surface or intracellularly in hyaline cells of Sphagnum (Basilier, 1974). Many subsequent studies have confirmed this finding and assign the photoautotrophic cyanobacteria a prominent role in BNF in mosses also in non-peatland mosses (Carrell et al, 2019;Klarenberg et al, 2022;Rajandu et al, 2021;Renaudin et al, 2022a;van den Elzen et al, 2020). However, other studies reported that members of the phyla Acidobacteria, Actinobacteria, Alphaproteobacteria, Bacteroidetes, Betaproteobacteria, Eremiobacterota and Verrucomicrobiota can also contribute to BNF in mosses (Holland-Moritz et al, 2021;Vile et al, 2014).…”
Section: Introductionmentioning
confidence: 98%